PhI(OAc)2-Promoted Regioselective Cycloaddition of N-Aminopyridinium Ylides with Electron-Deficient Alkenes - Wang, Junlei; Chen, Guiling; Shi, Chengcheng; Xie, Qinglin; Gao, Guocheng; Li, Yanan; Du, Haijun; Cai, Xiaohua; Li, Hongqing; Huang, Binbin (Synlett, 2024)
Herein, we report a regioselective cycloaddition strategy of N-aminopyridinium ylides with electron-deficient alkenes, in the presence of a hypervalent iodine reagent, PhI(OAc)2. A variety of multifunctionalized pyrazolo[1,5-a]pyridine architectures were smoothly afforded by the reactions of pyridine-, quinoline-, and isoquinoline-based N-ylides with diverse alkenes with or without a halogen atom adjacent to the electron-withdrawing group (EWG) under facile conditions.
Keywords: regioselective; cycloaddition; N-aminopyridinium; alkenes